Variability in grain quality traits of aromatic rice (Oryza sativa L.) (Bangladesh Journal of Agricultural Research, 2013)
The present study involved the evaluation of physio-chemical characters and cooking quality of 36 rice genotypes from Madhya Pradesh and Chhattisgarh. The fine grain genotypes like Rajim-12, Kalimuchh, and Munibhog were found good for moderate kernel length and L:B ratio; Rajabhog, Jhulari, and Baghmuchha for kernel length after cooking and L:B ratio of cooked rice Kalajira and Bikoni for head rice recovery%; Barang, Bantaphool, Gangabalu, and Bikoni for elongation ratio; Barang, Rajabhog, Gangabalu, Bikoni, and Chirainikhi for elongation index; Sonth, Rajim-12, Jhulari, Gangabalu, Jhilli Safri, and Bikoni for intermediate alkali values. These genotypes may be utilized as donors for improvement of quality traits. In the present study, superior genotypes were Rajm-12 for grain yield, kernel length, L:B ratio and kernel length after cooking; Rajabhog for grain yield, kernel length after cooking, L:B of cooked rice and elongation index; Bikoni for head rice recovery, elongation ratio, elongation index, and intermediate alkali values. DOI: http://dx.doi.org/10.3329/bjar.v37i4.14352 Bangladesh J. Agril. Res. 37(4): 551-558, December 2012